From modernism to postmodernism : American poetry and theory in the twentieth century - Ashton, Jennifer, 1964- (Cambridge studies in American literature and culture, 2006)
In this overview of twentieth-century American poetry, Jennifer Ashton examines the relationship between modernist and postmodernist American poetics. Ashton moves between the iconic figures of American modernism - Stein, Williams, Pound - and developments in contemporary American poetry to show how contemporary poetics, specially the school known as language poetry, have attempted to redefine the modernist legacy. She explores the complex currents of poetic and intellectual interest that connect contemporary poets with their modernist forebears. The works of poets such as Gertrude Stein and John Ashbery are explained and analysed in detail. This major account of the key themes in twentieth-century poetry and poetics develops important ways to read both modernist and postmodernist poetry through their similarities as well as their differences. It will be of interest to all working in American literature, to modernists, and to scholars of twentieth-century poetry.